(untitled) (Universal International Scientific Journal, 2026)
The dependence of the potential barrier height at the boundary surface of crystallites in the Por-Si layer on crystallite size, alloying concentration, and temperature was studied numerically. Also, taking into account the dependence of the carrier mobility on crystallite size and potential barrier height, various graphs of the volt-ampere characteristic for the Por-Si layer were obtained.